2022
DOI: 10.3390/coatings12070985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of WC on the Microstructure, Wear and Corrosion Resistance of Laser-Deposited CoCrFeNi High Entropy Alloy Coatings

Abstract: Wear and corrosion resistant properties of high entropy alloy coatings (HEAC) on H13 steel are of particular interest for industrial applications. The CoCrFeNi HEA/WC composite coatings (HEACC) developed in this study were successfully prepared by incorporating 10–40 wt.% WC into a matrix of CoCrFeNi HEA using laser cladding on an H13 steel substrate. Phase transformation, microstructure evolution, microhardness, wear and corrosion resistance of CoCrFeNi HEACC were investigated. According to the results, all C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…After the AM process, all of presented only FCC phases, independent of laser power. Thus, the LMD meth to produce an in situ alloy with the desirable FCC HEA microstructure from metal powders [28,29]. During the laser deposition process, residual stress was after the rapid melting and cooling of the deposition layers, changing the lattic Thus, the migration and intensity of the main peaks were affected [32].…”
Section: Phase Characterization Using Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…After the AM process, all of presented only FCC phases, independent of laser power. Thus, the LMD meth to produce an in situ alloy with the desirable FCC HEA microstructure from metal powders [28,29]. During the laser deposition process, residual stress was after the rapid melting and cooling of the deposition layers, changing the lattic Thus, the migration and intensity of the main peaks were affected [32].…”
Section: Phase Characterization Using Xrdmentioning
confidence: 99%
“…[21] studied the microstructural evolution of untreated LMD Al 0.3 CoCrFeNiNb 0.5 HEA with the highest average hardness of 715 HV0.5. The microstructure and mechanical properties of LMD-prepared CoCrFeNi HEAs with the addition of Si [22], Mn [23][24][25][26][27], WC [28], and Al [29] were also studied to improve its micro-mechanical properties [30] or comprehensive performance [31]. Additionally, the LMD process itself has also been seen to affect the mechanical properties of bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…These elements usually have strong slagging and deoxidation abilities, which is conducive to improving the wear resistance and processability of the coating. Bingqian Wu et al [36] studied the effect of Si content on the microstructure and wear resistance of FeCoCr 0.5 NbSi 0.4 HEA coatings; the results showed that with the increase of Si content, the microstructure of the coating changed obviously, the M 2 B phase decreased, the eutectic structure also disappeared gradually, and the wear resistance of the coating at FeCoCr 0.5 NbSi 0.4 was the best. During wear, the phases with low hardness values are fatigued off by the cyclic action of the WC balls, while the phases with higher hardness are not worn off, which shows that the wear mechanism of the FeCoCr 0.5 NiBSi 0.4 high-entropy alloy coating is mainly fatigue wear.…”
Section: The Chemical Composition System Of Laser Cladding Hea Coatingsmentioning
confidence: 99%
“…Apparently, the materials used in marine parts are supposed to obtain a combination of desirable properties such as high strength and ductility, high resistance to wear, corrosion and CE, while this combination is difficult to co-exist in a single bulk material, and even it does, manufacturing costs might be high. Fortunately, surface modification techniques [14][15][16][17] provide an effective way to solve the above problems through tailoring the surface properties while retaining the bulk properties. During the past decades, the development of surface modification against the wear, high-temperature oxidation and CE primarily relied on the protective coating with extensively expensive elements.…”
Section: Introductionmentioning
confidence: 99%